Gabriel Badea-Paun (Confluenţe Bibliologice, 2020)
The article presents a remarkable history with approaches to Art History, but with interesting studies related to the Royal Family. Gabriel Badea-Păun, a Romanian-French writer, has created a very professional work, full of information, but very entertaining for anybody even slightly interested in art and expecially portraiture.This article represents a wide range comprehensive information on how the leading class wanted to be immortalized throughout the XIX and the XX century (covering from the end of the XVIII century to the mid of the XX). Romanian and foreign museums have organized exhibitions of documents related to the historiography of Romanian art, interesting studies on the Royal Family, awarded in various competitions.
Keywords: Gabriel Badea-Păun; royal dynasties